HUBUNGAN PERAN PEMBIMBING KLINIK DENGAN METODE PROBLEM BASED LEARNING PADA MAHASISWA KEBIDANAN DI RSUD CIBINONG - Dina Martha Fitri; Nurhidayah Nurhidayah (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2020)
PBL or problem based learning is a learning approach that uses real-world problems as a context for students to learn about critical thinking and problem-solving skills for which a clinical counselor is needed. So the purpose of research to find out "The relationship of clinical counselor role with the method of Problem Based Learning on the students practice at RSUD Cibinong in December 2017 July 2018. This research method used a quantitative research design using cross sectional approach in July 2018 population of all students who practice at RSUD Cibinong 2018 with a sample of 52 people. The data taken are primary data by using questionnaires that have been validated and reability after data obtained in data though using univariate analysis with frequency distribution and bivariate analysis using chi-square test. The results showed that PBL method was achieved as much as (73.1%), while the other 26.9% had not been able to achieve the problem based learning method. The role of clinical counselor as educator (51,9%), as role model as much (55,8%), facilitator as much (71,2%) and role as evaluator as much (59,6%). From the result of the research, it can be concluded that there is a significant relationship between problem based learning method with the role of clinical counselor as educator (p = 0,000) and facilitator (p = 0,041) and no relation on role model role (p = 0,453) and evaluator role p = 0.677). The conclusions of the research conducted at RSUD Cibinong mostly achieved. In this research is expected role of clinical counselor as role model can exemplify good behavior in learners and can do evaluation in structured and make improvement based on evaluation result